Adverse body composition and lipid parameters in patients with prolactinoma: a case-control study - Posawetz, Anna Sophia (BMC Endocr Disord, 2021)
BACKGROUND: Hyperprolactinaemia might cause adverse metabolic effects. The aim of our study was to compare parameters of body composition, glucose and lipid metabolism between untreated patients with prolactinoma and controls and to assess changes after initiation of cabergoline. METHODS: Case-control study with a retrospectively analyzed follow-up in patients with prolactinoma after initiation of cabergoline therapy. RESULTS: 21 patients with prolactinoma (9 micro- and 12 macroprolactinomas; 7 females) and 30 controls were analyzed. Patients with prolactinoma had significantly higher BMI than controls; fat mass did not differ between groups. Only men - but not women - with prolactinoma had significantly higher fat mass at all six sites measured compared to controls. Levels of LDL (130 (107–147.5) vs. 94.5 (80–127.5) mg/dl, p < 0.001) were significantly higher, levels of HDL (56 ± 16.7 vs. 69.2 ± 14.6 mg/dl, p = 0.004) significantly lower than in controls. Fasting glucose, HOMA-IR, HbA1c, adiponectin, CRP, and homocysteine did not differ between groups. After a median of 10 weeks (IQR 7–18 weeks) after initiation of cabergoline, total (from 212.5 ± 36.2 to 196.9 ± 40.6 mg/dl, p = 0.018) and LDL cholesterol (130 (107–147.5) to 106.5 (94.3–148) mg/dl, p = 0.018) had significantly decreased. Analyzing men and women separately, this change occurred in men only. CONCLUSIONS: Reasons for the association between prolactin and metabolic parameters include direct effects of prolactin on adipose tissue, hyperprolactinaemia-triggered hypogonadism and dopamine-agonist therapy per se. Altered lipid metabolism in patients with prolactinoma might imply an increased cardiovascular risk, highlighting the necessity to monitor metabolic parameters in these patients.